Regional Integration of Stock Exchanges in Eastern and Southern Africa : Progress and Prospects - Irving, Jacqueline (IMF Working Papers; Working Paper ;, 2005)
This paper assesses whether regional cooperation and integration of stock exchanges in eastern and southern Africa could offer a way of overcoming impediments to the exchanges' development. The paper concludes that regional cooperation and, at a later stage, integration, if carried out at the right pace and in a pragmatic way, could improve the liquidity, efficiency, and competitiveness of these exchanges. Further progress in developing national financial markets must precede any actual moves to integrate securities markets. These exchanges could meanwhile benefit from closer cooperation, including by encouraging more crossborder listings and information/technology sharing.